Bargaining costs in a common pool resource situation – the case of reindeer husbandry and forestry in northern Sweden - Widmark, Camilla (NRC Research Press (a division of Canadian Science Publishing), 2018)
This paper describes the development and implementation of a model to measure and compare transaction costs in situations of multiple-land use, where interdependence prevails between the agents â thus actions of one agent affects others. Transaction costs typically occur in situations where limited resources are used by more than one agent and bargaining of the use is conducted to mitigate conflict. The model of the paper is empirically tested on one such situation: forestry and reindeer husbandry, which is pursued in northern Sweden where transaction costs occur in common land use as a result of consultations. The results indicate that transaction costs are unevenly distributed between the two agents, where reindeer husbandry carries the highest costs resulting in uneven power relations. Transaction costs are driven by the presence of Land Use Plans of reindeer husbandry, interestingly enough driving the costs in different directions for the two agents. The model illustrates the elements of transaction costs in a common pool resource situation, and the results are not only useful for this specific situation in policymaking, but also to other similar situations. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.